The influence of training age on the annual development of physical qualities within academy rugby league players - Till, K.; Darrall-Jones, J.; Weakley, J. J.; Roe, G. A.; Jones, B. L. (The Journal of Strength and Conditioning Research, 2017)
Previous research in academy rugby league players has evaluated the development of physical qualities according to chronological age. However, no study has considered the training age, defined as the number of formalized years of strength and conditioning training, of these players. Therefore, the purpose of this study was to present and compare the annual changes in physical qualities of academy rugby league players according to training age. Sixty-one academy players undertook a fitness testing assessment, including anthropometric (height, body mass, sum of 4 skinfolds) and physical (10 and 20 m sprint, 10m momentum, vertical jump, Yo-Yo intermittent recovery test level 1 [Yo-Yo IRTL1], one-repetition maximum [1RM] squat, bench press and prone row) measures at the start of preseason on 2 consecutive annual occasions. Players were categorized into one of 3 training age groups (i.e., 0, 1, or 2 years) and were analyzed using magnitude-based inferences. Almost certain, very likely or likely annual improvements were identified for body mass, 10m momentum, Yo-Yo IRTL1, vertical jump, and all strength measures for the 3 training age groups. When training age groups were compared, 1 year showed possibly or likely lower strength increases than 0 years training age. However, the 2 years training age group demonstrated possibly or likely increased strength changes compared with 1 year. These findings suggest that training age is an important consideration for strength and conditioning practitioners but it is likely to be a combination of chronological age, biological maturity, and training experience alongside dynamic interplayer variability that influences the physical development of academy rugby league players.